The Role of Customer Empowerment in Development His Equity for The Firm through of Mediating Relationship Quality: Empirical Study on Customers of Mobile Telecommunications Firms in Syria - Ragab, Jihan; Masry, Mohamad (The Arab Journal of Administration, 2019)
The research aims to presenting a vision that describes the role of customer empowerment in devel- opment his equity for the firm through of mediating relationship quality, in order to help businesses, adopt and activate an approach of customer empowerment so that contribute to promotion relationship quality between organization with customers and development customer equity for organization. Research community includes all customers of mobile telecommunications firms in Syria) Syriatel, MTN(, and relied on the interceptor sample at ranches of the two companies, where was distribution )384( questionnaires and number of valid lists for analysis )331( in response rate 86%, were processed using sta- tistical methods suitable for research objectives. Found the research results a significant extreme impact to customer empowerment with its four di- mensions )influence, meaning, freedom of choice, and self-efficacy(, )according to its importance( on the quality of the customer relationship with the service provider organization, and existence a significant ex- treme impact of the quality of the relationship )satisfaction, confidence(, )depending on its importance( on the equity added by the customer to the service provider organization, in addition to existence a signif- icant extreme impact of customer empowerment with its four dimensions )influence, meaning, freedom of choice, self-efficacy(, )ranked by importance( on the customer equity, and existence a significant impact of relationship quality as an mediator variable on the relationship between customer empowerment and customer equity.